2015
DOI: 10.1063/1.4926548
|View full text |Cite
|
Sign up to set email alerts
|

Light-trapping optimization in wet-etched silicon photonic crystal solar cells

Abstract: We demonstrate, by numerical solution of Maxwell's equations, near-perfect solar light-trapping and absorption over the 300-1100 nm wavelength band in silicon photonic crystal (PhC) architectures, amenable to fabrication by wet-etching and requiring less than 10 lm (equivalent bulk thickness) of crystalline silicon. These PhC's consist of square lattices of inverted pyramids with sides comprised of various (111) silicon facets and pyramid center-to-center spacing in the range of 1.3-2.5 lm. For a wet-etched sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The rear passivation layer is implemented as a 50 nm SiO 2 (n = 1.45) layer. This reduces parasitic absorption losses in real-world back contact such as silver [13] and justifies our modeling of the back-reflector as a PEC. We apply periodic boundary conditions (PBC) along x and y−directions and put perfectly matched layers (PML) at the computation boundaries normal to the z−direction.…”
Section: 43%supporting
confidence: 65%
See 2 more Smart Citations
“…The rear passivation layer is implemented as a 50 nm SiO 2 (n = 1.45) layer. This reduces parasitic absorption losses in real-world back contact such as silver [13] and justifies our modeling of the back-reflector as a PEC. We apply periodic boundary conditions (PBC) along x and y−directions and put perfectly matched layers (PML) at the computation boundaries normal to the z−direction.…”
Section: 43%supporting
confidence: 65%
“…Unlike the classical pyramid arrays with 10µm base lengths [23] that can be described by ray-optics, we consider the largely unexplored regime of micro-pyramid photonic crystals with wavelength-scale features and novel wave-optics phenomena. Using a rigorous FDTD solution of Maxwell's equations, light-trapping and absorption beyond the Lambertian limit was demonstrated [13] in an optimized 10 µm thick c − Si inverted micro-pyramid PhC. The optimum lattice constant in this case is 2500 nm, yielding a MAPD of 42.5 mA/cm 2 .…”
Section: 43%mentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to explore nano-imprinting methods for the fabrication of thin-film, inverted-cone photonic crystals. It is also of interest to study the possibility of deposition of perovskites onto thin-film Silicon photonic crystals 31 to realized very high-efficiency tandem solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent simulation revealed that a set of nanostructured silicon (with substrate thickness of 3–8 μm) can achieve a short‐circuit current of 42.5 mA cm −2 by optimizing the inverted nanopyramid structure, as shown in Figure b. Compared with that for currently utilized few‐hundred‐micrometer‐thick‐silicon textured solar cells, where high‐quality Si is required to achieve a similar short‐circuit current density, as shown in Figure c,d, the requirement of silicon quality for high‐performance solar cells with low weight may be relaxed. It has been reported that many forms of nanostructured silicon, such as nanopillars, inverted nanopyramids, and nanoholes, enable light harvesting.…”
Section: Nanostructured Silicon For Flexible Solar Cellsmentioning
confidence: 99%